Sex Differences in Relationships Between Perceived Coach-Induced Motivational Climates, Basic Psychological Needs, and Behavior Regulation Among Young Swimmers. Issue 5 (October 2020) - Rodrigues, F.; Macedo, R.; Cid, L.; Teixeira, D. S.; Marinho, D. A.; Monteiro, D.
This study analyzed independent and codependent effects of task- and ego-involving motivational climates on basic psychological need satisfaction and behavioral regulation (i.e., autonomous and controlled motivation) among young athletes. Participants were young Portuguese female ( n = 114) and male ( n = 324) swimmers, nested within four different clubs. Participants completed a multisection survey, assessing motivational climates, basic psychological needs satisfaction, and behavioral regulation. We used polynomial regression analysis with surface response methodology to analyze the interactions between these constructs. We found that perceived task- and ego-involving motivational climates were not mutually exclusive; rather, their relationship depended on how athletes perceived coaches' behaviors and how coaches emphasized one or both climates. Coaches who fostered both motivational climates promoted positive outcomes among male (but not female) athletes.